Analysis of energy management strategies for series hybrid electric vehicles (Вестник транспорта - Transport xabarnomasi, 2025)
This paper focuses on the brief overview of available energy management strategies (EMS) for series hybrid electric vehicles. Alternatively, according to the mechanism that determines the control action, EMSs can be put into groups of rule-based and optimization-based methods. Each control method from each group has been extensively explained and compared in terms of advantages and disadvantages. The main goal of this section is to highlight important research gaps in the field as well as contribute to the increasing list of review debates.